2001
DOI: 10.2460/ajvr.2001.62.1255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lithium dilution cardiac output as a technique for measurement of cardiac output in dogs

Abstract: The LiDCO technique is a suitable substitute for TDCO to measure cardiac output in dogs. Use of LiDCO eliminates the need for catheterization of a pulmonary artery and could increase use of cardiac output monitoring, which may improve management of cardiovascularly unstable animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
119
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(121 citation statements)
references
References 19 publications
1
119
1
Order By: Relevance
“…Quandt et al (1998), in dogs anesthetized with a single dose of propofol and using thermodilution, did not observe depressant effects of this drug on CO and showed stability of CO. Ilkiw & Pascoe (2003), in a study with cats anesthetized with a propofol infusion, concluded that this drug alone provided cardiopulmonary stability. Although Mason et al (2001) states that higher and lower CO influences the degree of agreement between methods, cardiac output values were stable in this study, thus the influence of the level of CO on the degree of agreement could not be determined.…”
Section: Discussioncontrasting
confidence: 49%
“…Quandt et al (1998), in dogs anesthetized with a single dose of propofol and using thermodilution, did not observe depressant effects of this drug on CO and showed stability of CO. Ilkiw & Pascoe (2003), in a study with cats anesthetized with a propofol infusion, concluded that this drug alone provided cardiopulmonary stability. Although Mason et al (2001) states that higher and lower CO influences the degree of agreement between methods, cardiac output values were stable in this study, thus the influence of the level of CO on the degree of agreement could not be determined.…”
Section: Discussioncontrasting
confidence: 49%
“…The potential for accumulation of lithium, especially during diminished CO, also limits the total number of time points we could assess through the course of the experiment. We did not use other methods for determining CO (e.g., thermodilution, partial CO 2 rebreathing); however, lithium dilution CO has been validated in multiple species, including dogs, and found to be more precise than thermodilution when compared with electromagnetic flowmetry in pigs (11)(12)(13)(14)(15). Another concern is the potential for interference or damping of the arterial pressure waveform secondary to problems with the arterial catheter or transducer.…”
Section: Discussionmentioning
confidence: 97%
“…The lithium dilution technique produces precise and accurate values of cardiac output and has been validated in multiple species, including dogs (11)(12)(13)(14)(15). Similar to other indicator dilution techniques (cold saline, indocyanine green), CO is determined at a single point in time.…”
mentioning
confidence: 99%
“…This technique is now well established and has been validated in humans, 3,4 horses, 5,6 pigs, 7 and dogs. 8 The main advantages of the LiDCO system over thermodilution are the avoidance of pulmonary artery catheterization with its associated hazards and simpler instrumentation. Furthermore, a catheterized peripheral vein can be used to inject the lithium indicator, 9,10 eliminating the need for central venous catheterization in patients that do not warrant it.…”
mentioning
confidence: 99%